Difficulty and discrimination of ordinary exams in the Subject: Cells, Tissues, and Integumentary System in Basic Sciences - Armando Carrazana Lee; Guadalupe Álvarez Bustamante; Madelem Quesada Rodríguez; Yahumara Hidalgo Cerito (Universidad de Ciencias Médicas de La Habana, 2018)
Introduction: It is necessary to create an evaluation system upon the most solid standards in order to make emphasis on the importance that the instruments used in the controls have the required quality, and the possibility to be tested. Objective:To identify the level of difficulty and the power of discrimination of the exams applied in the Subject: Cell, Tissues and Integumentary System, corresponding to the "D" Plan in the University of Medical Sciences of Havana, in the 2016-2017 academic year. Material and Methods: Difficulty and discrimination indexes were calculated, as well as the coefficient of discrimination of each topic in the two different sets used in the ordinary exam. Teachers and outstanding students were interviewed as key informants, and their criteria were compared. Results:Of the 14 questions presented in both sets, two of them were very difficult (14.3%), five were moderately difficult (35.7%), and seven of them presented an average difficulty (50%). Thus, the difficulty index of the test in set A was 0.51 and the discrimination index was 0.22, whereas in set B they were 0.42 and 0.25 respectively, which classifies the exam in general from moderately difficult to highly difficult, result that should be directed towards a regular elaboration of questions. The coefficient of discrimination for all topics was always positive, so it was considered adequate. Thus, in set A it ranged between 0.20 and 0.63, whereas in set B it ranged between 0.18 and 0.66. Conclusions: The instruments applied ranged between moderate difficulty to high difficulty, from a poor to regular power of discrimination. Keywords: Difficulty Index, Power of Discrimination, Evaluation of Learning.